2007
DOI: 10.1354/vp.44-5-600
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Characterization of Multidrug Resistance P-glycoprotein, Alpha Fetoprotein, and Neovascular Endothelium-Associated Antigens in Canine Hepatocellular Carcinoma and Cirrhotic Liver

Abstract: Abstract. P-glycoprotein (P-gp), which is encoded by the multidrug resistance gene (MDR-1); alpha fetoprotein (AFP); and vascular endothelium-associated antigens are well-known markers for human and canine hepatic diseases. We obtained liver tissues from 5 dogs with hepatocellular carcinoma (HCC) and 12 dogs with cirrhosis, and we performed histopathologic and immunohistochemical evaluations using anti-P-gp, anti-AFP, anti-CD31, and anti-CD34 antibodies. P-gp was expressed at higher levels in HCC than in cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…IHC was performed as described previously with a few modifications [28]. Briefly, slides were deparaffinized in xylene then hydrated in graded ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…IHC was performed as described previously with a few modifications [28]. Briefly, slides were deparaffinized in xylene then hydrated in graded ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…[5] [7] From various studies it was found that P-gp was more highly expressed in HCC (hepatocellular carcinoma) than in cirrhotic liver, which is consistent with the known resistance of HCC to chemotherapy. [5] RT-PCR can be one of the most sensitive, efficient, fast, and reproducible methods of measuring gene expression. RT-PCR can be used to quantify mRNA levels from much smaller samples.…”
Section: Discussionmentioning
confidence: 78%
“…P-gp is normally expressed in tissues with excretory function, including the jejunum, kidney, liver, and adrenal gland. [5] Over-expression of MDR1 will result in increased drug efflux activity of P-gp leading to multi-drug resistance (MDR).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-CD34 is considered the best immuno-histochemical endothelial marker for tricolor staining (Cui and Hano, 1996). Other detailed references can refer to Pusztaszeri et al (2006) and Tashbaeva et al (2007).…”
Section: Materials and System Overview Microscopic Image Samples Of Omentioning
confidence: 99%